An overall view of the most common experimental models for multiple sclerosis - S. Dedoni; M. Scherma; C. Camoglio; C. Siddi; L. Dazzi; R. Puliga; J. Frau; E. Cocco; P. Fadda (Neurobiology of Disease, 2023)
Multiple sclerosis (MS) is a complex chronic disease with an unknown etiology. It is considered an inflammatory demyelinating and neurodegenerative disorder of the central nervous system (CNS) characterized, in most cases, by an unpredictable onset of relapse and remission phases. The disease generally starts in subjects under 40; it has a higher incidence in women and is described as a multifactorial disorder due to the interaction between genetic and environmental risk factors. Unfortunately, there is currently no definitive cure for MS. Still, therapies can modify the disease’s natural history, reducing the relapse rate and slowing the progression of the disease or managing symptoms.The limited access to human CNS tissue slows down. It limits the progression of research on MS. This limit has been partially overcome over the years by developing various experimental models to study this disease. Animal models of autoimmune demyelination, such as experimental autoimmune encephalomyelitis (EAE) and viral and toxin or transgenic MS models, represent the most significant part of MS research approaches. These models have now been complemented by ex vivo studies, using organotypic brain slice cultures and in vitro, through induced Pluripotent Stem cells (iPSCs). We will discuss which clinical features of the disorders might be reproduced and investigated in vivo, ex vivo, and in vitro in models commonly used in MS research to understand the processes behind the neuropathological events occurring in the CNS of MS patients. The primary purpose of this review is to give the reader a global view of the main paradigms used in MS research, spacing from the classical animal models to transgenic mice and 2D and 3D cultures.